The effect of comorbidity on mortality in elderly patients undergoing emergency abdominal surgery: A systematic review and metaanalysis - Çinar, F.; Parlak, G.; Eti, Aslan, F. (Turkiye Klinikleri, 2021)
Background/aim: With the increase in the elderly population, the elderly proportion needing emergency surgery is also increasing. Despite medical advances in surgery and anesthesia, negative postoperative outcomes and high mortality rates are still present in elderly patients undergoing emergency surgery. Comorbidities are described as the main determining factors in poor outcomes. In this metaanalysis, it was aimed to investigate the effect of comorbidity on mortality in elderly patients undergoing emergency abdominal surgery. Materials and methods: The studies published between 2010-2019 were scanned from databases of Google Scholar, Cinahl, Pub Med, Medline and Web of Science. Quality criteria proposed by Polit and Beck were used in the evaluation of the included studies. Interrater agreement was calculated by using the Kappa statistic, effect size by using the odds ratio, and heterogeneity among studies by using the Cochran’s Q statistics. Kendall’s Tau-b coefficient and funnel plot were used to determine publication bias. Results: A total of 9 studies were included in the research. There was a total of 1330 cases in the studies. The total mortality rate was 21% (n = 279), the total rate of having a comorbid factor was 83.6% (n = 1112), and the rate of having a comorbid factor in mortality was 89.2% (n = 249). According to the fixed effects model, the total effect size of comorbid factors on causing mortality was not statistically significant with a value of 1.296 (C.I; 0.84-1.97; P > 0.05). Conclusion: Our study revealed that comorbidity had no significant effect on causing mortality in geriatric patients undergoing emergency abdominal surgery. There are controversial results in the literature, and in order to reach more precise results, studies involving wider groups of patients and further studies examining the specific effect of certain comorbid conditions are needed. © TÜBİTAK.
Keywords: Emergency; Abdominal surgery; Elderly; Mortality; Comorbid